Technology and delivery of justice: with reference to court recording transcription - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2019)
The technology in the courtrooms has brought much ease to the judges and the parties. Unlike the taking of notes of evidence manually which is a tedious job that can take countless hours of toil, the electronic gadget recording or the CRT have allowed speedy disposal of court cases. Instead of spending time writing notes of evidence in verbatim, the trial judge would be able to fully concentrate on the trial including the examination of witnesses and ascertaining their demeanour.